Macrolides at Clinically-Relevant Concentrations May Induce Biofilm Formation in Macrolide-Resistant Staphylococcus aureus - Carlos F. Amábile-Cuevas (MDPI AG, 2023)
Macrolides inhibit biofilm formation in several Gram-negative, intrinsically-resistant bacterial species. However, the effect of macrolides upon biofilm formation by susceptible Gram-positive bacteria has been much less explored as such concentrations also inhibit cell growth. To circumvent this problem, the effect of macrolides (erythromycin, clarithromycin and azithromycin) at 0.5-2 µg/mL, upon biofilm formation, was explored on macrolide-resistant Staphylococcus aureus isolates, using the crystal violet assay with 96-well plates. Early (4 h) biofilm formation by strains having constitutive target-modification resistance was consistently induced by all macrolides but not in azithromycin-treated cells in longer (8 and 12 h) incubation. In inducible-resistance isolates, early biofilm formation was enhanced by some macrolide treatments, compared to similar cell growth in the absence of antibiotics; but the typical decay of biofilms at longer incubation appeared prematurely in macrolide-treated cultures. Biofilm formation in an efflux-mediated resistant isolate was not affected by macrolides. These results indicate that macrolides induce the formation of biofilm by resistant S. aureus isolates, especially during the early stages. This suggests that the empirical use of macrolides against infections caused by resistant S. aureus strains could not only result in clinical failure but even in the enhancement of biofilms, making further treatment difficult.